2014
DOI: 10.1016/j.bbrc.2014.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell proliferation, migration and invasion of B16-F10 melanoma cells by α-mangostin

Abstract: a b s t r a c tIn this study, we have evaluated the potential antineoplastic effects of a-mangostin (a-M), the most representative xanthone in Garcinia mangostana pericarp, on melanoma cell lines. This xanthone markedly inhibits the proliferation of high-metastatic B16-F10 melanoma cells. Furthermore, by deeply analyzing which steps in the metastatic process are influenced by xanthone it was observed that a-M strongly interferes with homotypic aggregation, adhesion, plasticity and invasion ability of B16-F10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Of these compounds, α -mangostin was shown to have the strongest apoptotic activity in human melanoma cells and, compared to other similar compounds, α -mangostin was shown to be the most effective agent in human cancer cell lines [ 27 , 28 ]. α -Mangostin has also been reported to act as an anticancer agent against various types of cancer cells including canine osteosarcoma cells, human colorectal cancer cells, and pancreatic cancer cells [ 6 , 29 32 ]. This suggests that α -mangostin may be considered a prospective anticancer agent; however, the biological mechanism underlying α -mangostin-induced cell death in human OSCC cell lines has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Of these compounds, α -mangostin was shown to have the strongest apoptotic activity in human melanoma cells and, compared to other similar compounds, α -mangostin was shown to be the most effective agent in human cancer cell lines [ 27 , 28 ]. α -Mangostin has also been reported to act as an anticancer agent against various types of cancer cells including canine osteosarcoma cells, human colorectal cancer cells, and pancreatic cancer cells [ 6 , 29 32 ]. This suggests that α -mangostin may be considered a prospective anticancer agent; however, the biological mechanism underlying α -mangostin-induced cell death in human OSCC cell lines has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Our chemical study indicated the presence of various kinds of polyphenols and flavonoids [chlorogenic acid, (− )-EC, rutin, hyperoside, vitexin-2″-O-rhamnoside, procyanidin B2, and procyanidin C1] and triterpenes (oleanolic acid and ursolic acid) and as they were described previously for their antiproliferative activity against melanoma cells [7,[23][24][25][26][27][28], we believe that they are responsible at least in part for the antiproliferative potential of TOF extract. This finding is in good accordance with our previous studies that showed how C. azarolus ethyl acetate extract exerted a potent viability inhibition effect of high-metastasic B16F10 [7].…”
Section: Discussionmentioning
confidence: 91%
“…In our previous study, α -mangostin was demonstrated to have a potent anticancer effect in human oral squamous cell carcinoma cell lines (OSCC) through apoptosis and cell cycle arrest [ 19 ]. Also, α -mangostin has been reported to inhibit migration and invasion in various cancer cells, including melanoma cells, pancreatic cancer cells, and lung adenocarcinoma cells [ 17 , 29 31 ]. However, the effect of α -mangostin on human osteosarcoma cells is uncertain.…”
Section: Discussionmentioning
confidence: 99%